1993
DOI: 10.1117/12.148117
|View full text |Cite
|
Sign up to set email alerts
|

<title>Imaging spectrometry: concepts and system trade-offs</title>

Abstract: The concept of imaging spectrometry is finding broad application in scientific instrumentation for Earth-based, airborne, and space applications. An imaging spectrometer is characterized by the combination of imaging with complete sampling in the spectral domain. In so doing, material identification can be accomplished and displayed in conjunction with the conventional recognizable image.An imaging spectrometer incorporates a wide variety of technologies, including focal plane arrays, imaging and spectrometer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Virtual Conference 30 March-2 April 2021 a survey of the already existing hyperspectral imagers and innovative freeform designs to identify the most promising solutions to increase the compactness and the performance. Some survey of hyperspectral imagers has already been done in the past [29], [30]. However, the study performed in 1993 by Herring et al, is now outdated and cannot be used to identified state of art concepts.…”
Section: Icso 2020 International Conference On Space Opticsmentioning
confidence: 99%
“…Virtual Conference 30 March-2 April 2021 a survey of the already existing hyperspectral imagers and innovative freeform designs to identify the most promising solutions to increase the compactness and the performance. Some survey of hyperspectral imagers has already been done in the past [29], [30]. However, the study performed in 1993 by Herring et al, is now outdated and cannot be used to identified state of art concepts.…”
Section: Icso 2020 International Conference On Space Opticsmentioning
confidence: 99%
“…The Optical Path Difference (OPD) between the recombining beams linearly changes with the angle (slope) of the entering ray onto the instrument optical axis. It can be shown that the BS provides part of the phase-delay between the two interfering rays, the remaining part being originated outside the BS, and that the overall OPD linearly changes with varying the angle of the entering ray with respect to the instrumental optical axis [3][4][5]. Due to the absence of entrance slit the device acquires the image of the target superimposed to a fixed pattern of interference fringes.…”
Section: Instrument Conceptmentioning
confidence: 99%